Dysfunction Of Ninik Mamak In Enforcement Of Customary Sanctions: An Ethnographic Critical Study Of Violations Of Social Norms - Reflia Santika; Widiya Yul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study discusses the dysfunction of ninik mamak in the enforcement of customary sanctions against violations of social norms in Jambi Province, especially in one of the villages in Kerinci Regency. Ninik mamak traditionally plays the role of a customary authority holder whose function is to enforce norms, maintain tribal honor, and regulate social balance. However, the results of the study show that these roles are shifting and dysfunctional, especially when dealing with cases of moral violations such as infidelity. Through a critical ethnographic approach, this study reveals that the layered and rigid customary mechanism causes ninik mamak to not be able to directly sanction without going through a multi-level procedure. This condition hinders the effectiveness of customary social control functions and lowers the legitimacy of traditional authority in the eyes of the community. Analysis using Émile Durkheim's theory of social control and Max Weber's theory of traditional authority legitimacy shows that the dysfunction of ninik mamak is not only due to weak personal authority, but also due to customary social structures that are less adaptive to social change. Therefore, it is necessary to revitalize the role of ninik mamak so that customary institutions remain relevant and effective in maintaining norms and social solidarity in the midst of modernity.